2010
DOI: 10.1116/1.3292560
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the structural and optical quality of InN nanowires on Si(111) by molecular beam epitaxy

Abstract: The authors report on the growth and characterization of high quality InN nanowires on Si(111) by radio frequency plasma-assisted molecular beam epitaxy. InN nanowires with nontapered morphology were achieved with the use of an in situ deposited In seeding layer. They further examined the effects of the growth temperature, In/N flux ratio, as well as the thickness of the In seeding layer on the morphological, structural, and optical properties of InN nanowires grown directly on Si(111). It was observed that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…It is observed that the PL peak positions from the InN core region exhibit a consistent red-shift (up to ∼50 nm) with increasing temperature, which follows closely the calculated bandgap shift with temperature from Varshni's equation. This observation is also consistent with the superior crystalline quality and the near-intrinsic nature of the InN nanowires under the current growth conditions [7,8]. For comparison, such a clear red-shift has not been observed in InN nanowires with a large density of residue electrons [9,10].…”
Section: Optical Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…It is observed that the PL peak positions from the InN core region exhibit a consistent red-shift (up to ∼50 nm) with increasing temperature, which follows closely the calculated bandgap shift with temperature from Varshni's equation. This observation is also consistent with the superior crystalline quality and the near-intrinsic nature of the InN nanowires under the current growth conditions [7,8]. For comparison, such a clear red-shift has not been observed in InN nanowires with a large density of residue electrons [9,10].…”
Section: Optical Propertiessupporting
confidence: 84%
“…InN nanowires exhibit many important attributes, including a direct energy bandgap of ∼0.65 eV in the near-infrared spectral range, high electron mobility, and large saturation velocity [1], which are ideal for applications in infrared nanophotonics and nanoelectronics, including nanoscale lasers and photodetectors [2,3], ultrahigh speed nanowire transistors [2,4], and high efficiency solar cells [5,6]. Although significant progress has been made in the development of InN nanowires [7][8][9][10][11], there have been very few reports on the growth and characterization of In x Ga 1−x N ternary nanowires with x > 50% [15,16]. Additionally, to the best of our knowledge, the achievement of In-rich In x Ga 1−x N nanowires (x > 50%) epitaxially grown on InN nanowire templates has not been reported, and this has been identified as one of the major roadblocks for the development of practical InN-based devices.…”
Section: Introductionmentioning
confidence: 99%